Transformative Educational Research: Fleshing Out the Concepts - Luitel, Bal Chandra; Wagley, Shree Krishna (Journal of Education and Research, 2017)
In reference to this special issue, the idea of transformative educational research (TER) brings into light the integrated meanings on ‘the what’, ‘the why’, ‘the how’, ‘the who’, and ‘what next’ of transformative research approach in education, bringing together the ideas shared in the conference, and existing theoretical referents in this area of knowledge/practice. This concept note, thus, primarily seeks to define transformative research approach in education, taking into consideration what an associated research and practitioner agenda might look like. So as to achieve this purpose, this paper frames TRE practices so far, and creates space to think on future directions for education, and educational research through different sub-headings: (1) TER as multidimensional approach, (2) TER as a response to paradigm shift, (3) TRE as arts-based multi-paradigmatic space, (4) TER for emerging leaders at various spheres of life-world, and (5) TER as imagining the world beyond the given.